Event detection and analysis of a dense three-component near-summit seismic array deployed at Erebus volcano - Jaski, Erika, author; Aster, Richard C., advisor; Schutt, Derek, committee member; Cheney, Margaret, committee member (Colorado State University. Libraries, 2022)
Erebus volcano on Ross Island, Antarctica has maintained an erupting phonolitic lava lake for at least five decades. During active periods, the lava lake hosts large (up to ~10-m diameter) gas slugs rising through the conduit that create impulsive Strombolian eruptions and produce very long period (VLP) signals on broadband seismograms. We combine near-summit broadband observations and reanalyze data from a 100-station three-component short-period (4.5 Hz geophones) network deployed in an approximately 3 by 3 km region around the Main Crater during December 2008. Lava lake eruption template events are identified on broadband seismograms from their characteristic and repeating VLP spectral signature of nonharmonic modes between 0.033 and 0.2 Hz. Multi-channel and multi-station waveform matched filter correlations are performed across the short-period network using template events and correlation values that are three or more standard deviations are extracted into a working Inner Crater event catalogue, yielding 819 event detections over 19 days. While 94% of the signals in this catalogue are unique, 17 "families" of repeating lava lake events can also be identified through similar waveforms determined by Ward clustering on 5 stations, which are further interpreted for trends in location, size, and occurrence. We observe time-varying quasi-Poissonian interevent times and an approximately power-law size-frequency distribution with an excess of small events. Investigating the various event families that transpire in the Inner Crater region contributes to improved characterization and understanding of the seismogenic behavior of the lava lake degassing system and assists in the creation of a workflow that can be applied in volcanic and other circumstances that generate prolific low-level impulsive seismicity.
Zip file contains data spreadsheet and all_code files.